Predominance of Nonatherosclerotic Internal Elastic Lamina Calcification in the Intracranial Internal Carotid Artery. Issue 1 (January 2016) - Vos, Annelotte; Van Hecke, Wim; Spliet, Wim G.M.; Goldschmeding, Roel; Isgum, Ivana; Kockelkoren, Remko; Bleys, Ronald L.A.W.; Mali, Willem P.T.M.; de Jong, Pim A.; Vink, Aryan
Abstract : Background and Purpose—: Calcification of the intracranial internal carotid artery (iICA) is an independent risk factor for stroke. These calcifications are generally seen as manifestation of atherosclerosis, but histological investigations are limited. The aim of this study is to determine whether calcifications in the iICA are present in atherosclerotic plaques, or in other parts of the arterial wall. Methods—: Thirty-nine iICAs were histologically assessed, using digital microscopy to quantify the amount of calcification in the different layers of the arterial wall. Results—: Calcifications were found in the intima, around the internal elastic lamina and in the medial layer of the arterial wall. In 71% of the arteries, internal elastic lamina calcification contributed most to the total calcified cross-sectional surface area. Internal elastic lamina calcification was unrelated to the occurrence of atherosclerotic intimal lesions. Intimal calcifications were most often associated with atherosclerotic lesions, but also many noncalcified atherosclerotic lesions were found. Conclusions—: In the iICA, calcifications are predominantly present around the internal elastic lamina, suggesting that this nonatherosclerotic type of calcification contributes to the previously observed increased risk of stroke in patients with iICA calcifications. Abstract : Supplemental Digital Content is available in the text.